Dampak Ekonomi dan Lingkungan Ekspansi Perkebunan Kelapa Sawit (Studi Kasus: Desa Penyabungan, Kecamatan Merlung, Kabupaten Tanjung Jabung Barat, Jambi) - Rany Utami; Eka Intan Kumala Putri; Meti Ekayani (Institut Pertanian Bogor, 2017)
Oil palm is one of the major plantation commodity that earns foreign exchange. The expansion of oil palm plantation potentially gives not only economic benefits, but also the environmental problems. Therefore, the economic and environmental impacts of oil palm plantation expansion need to be assessed. This study uses revenue analysis to estimate the economic benefits, descriptive analysis to identify environmental impacts, and to estimate external costs using replacement cost and cost of illness. In this research, expansion is defined as the conversion of a part of or whole rubber plantation to oil palm plantation. The expansion resulted in farmers turning some or all of rubber gardens into palm oil plantations that resulted in an increase in revenues of 40.52%. In addition to the on-farm sector, farmers benefit from off-farm (24.46%) and non-farm (25.61%), bringing the total increase of farmers' income by 33.42%. Based on community perceptions of environmental impacts due to oil palm plantation expansion in the form of reduced quantity of groundwater, water pollution, and decreased animal population. The environmental impact of crude palm oil (CPO) factories is to produce liquid waste from palm oil processing that raises external costs for the community in the form of the replacement cost of clean water and the cost of illness